Conducta grafomotora y escritura cursiva en alumnos del segundo grado de primaria de una institución educativa del Callao - Astoquillca Mayhuire, Oliver (2010)
Descriptive-correlational research aims to establish a link between behavior graphomotor and cursive writing in school 2nd grade of a public school in La Perla-Callao. The sample has comprised of a total of 40 students from 7 to 8 years (22 males and 18 females), chosen intentionally. The instruments used are: sheets systematic observation of the Motion Graphics (Ajuriaguerra and Auzia, 1973) and Cursive (Condemarín and M. Chadwick), which considers the sub-test: run normal speed, fast speed of implementation and quality of copy. The research results show the existence of a weak positive relationship (r = 0.353) between behavior and cursive writing graphomotor featuring children between 7 and 8 years of age, where p <0.05.